Opportunities and Threats of the ChatGPT Revolution in Completing Students’ Final Assignments - Mansur, Aisyah; Amaliya, Winda; Lestari, Widya Ainun; Adiba, Fhathia (Journal of Education Reseach and Evaluation, 2025)
ChatGPT is an artificial intelligence-based chatbot that has attracted global attention due to its ability to generate coherent, systematic, and informative responses. The potential of ChatGPT to handle complex tasks, including in educational contexts, presents new challenges related to the opportunities and threats of its use in academic writing. This study aims to evaluate the effectiveness, efficiency, and impact of ChatGPT in completing students’ final assignments. The research employs a non-experimental quantitative approach with a descriptive design. The population consists of students from Universitas Negeri Makassar, with a randomly selected sample of 396 students. Data were collected through structured questionnaires and analyzed using descriptive statistics and Partial Least Squares-Structural Equation Modeling (PLS-SEM) to identify the influence of ChatGPT in academic contexts. The results indicate that ChatGPT plays a significant role in improving the quality and efficiency of final assignment completion. The use of ChatGPT helps students reduce mental burdens and stress often experienced during the writing process. However, concerns have also emerged regarding the increased risk of plagiarism and the potential for excessive dependence on this technology. The study concludes that there is a need for strict regulations from higher education institutions to ensure that the use of ChatGPT by students aligns with ethical principles and academic integrity. These findings have implications for the development of adaptive educational policies in response to advancements in artificial intelligence technology.